Characterizing Typologies of Polytraumatization: A Replication and Extension Study Examining Internalizing and Externalizing Psychopathology in an Urban Population. (November 2021) - Mekawi, Yara; Kuzyk, Eva; Dixon, H. Drew; McKenna, Brooke; Camacho, Luisa; de Andino, Ana Martinez; Stevens, Jennifer; Michopolous, Vasiliki; Powers, Abigail
A person-centered approach to examining trauma has uncovered typologies of polytraumatization that are differentially associated with psychopathology. However, previous research is limited by narrow conceptualizations of trauma, limited distal outcomes, and underrepresentation of racially marginalized groups. To address these gaps, we used latent profile analysis to uncover distinct polytraumatization typologies and examine four symptom-based (posttraumatic stress disorder, depression, aggression, and substance abuse) and two behavior-based (self-harm, jail counts) outcomes in a sample of adults with low socioeconomic resources ( N = 7, 426, 94% African American). The models were indicated by 19 traumatic experiences (e.g., accident, sexual assault, witnessing/experiencing violence). The best fitting model uncovered five classes: minimal trauma, physical abuse, violence exposure, sexual abuse, and polytrauma. Classes characterized by significant and varied trauma were higher on both internalizing and externalizing psychopathology, whereas those characterized by specific types of trauma were higher on only one type of psychopathology. Implications for the assessment and treatment of trauma-related disorders are discussed.